Translingual Negotiation Strategies Used by English Students to Build Classroom Interaction in a Translation Class - Roza, Veni (Lingua Cultura, 2019)
This research aimed at revealing what kind of translingual strategies that were practiced by the sixth-semester students to build interaction in the translation class. This qualitative research conducted through observing students’ interaction in translation class (using English, bahasa Indonesia, and Minangkabau languages). The researcher finds that four macro strategies proposed by Canagarajah (2013): envoicing, recontextualization, interactional, and entextualization strategies are consciously used by students during communication. Envoicing strategies are used by way of word coinage, foreignization, as well as code switching and code mixing dominantly by students while asking and clarifying information. Recontextualization  strategies are done through the use of the feature of linguistic form such formulaic Islamic greeting in Arabic preceding the talk. Interactional strategies used are confirmation check, check, clarification request, and recast. Interestingly more competent students use simplification in communication, and less competent speakers use leveling as entextualizationstrategies. The use of these strategies in speaking helps students (as speakers) to establish classroom interaction.